Leakages from macroprudential regulations: The case of household-specific tools and corporate credit - Apoorv Bhargava; Lucyna Górnicka; Peichu Xie (European Central Bank (ECB), 2023)
Sector-specific macroprudential regulations can increase the riskiness of credit to other sectors. First, using cross-country bank-level data we find that after a tightening of household-specific macroprudential policy during a credit expansion, banks with larger portfolios of residential mortgages increase their corporate lending by more than banks with smaller mortgage portfolios. Second, we compute three country-level measures of the riskiness of corporate credit allocation based on firm-level data. Consistently across the measures, an unexpected tightening of household-specific macroprudential tools during a credit expansion is followed by an increase in riskiness of corporate credit. These effects are quantitatively meaningful: the riskiness of corporate credit increases by around 10 percent of the historical standard deviation following an unexpected policy tightening. Further evidence from bank lending standards surveys suggests that the leakage effects are stronger for larger firms compared to SMEs, consistent with recent evidence on the use of personal real estate as loan collateral by small firms.
Keywords: G21; G28; G38; 330; Macroprudential regulations; sector-specific financial regulations; corporate credit risk; corporate loan growth